PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Packing Plant Celukan Bawang PT Semen Tonasa) - Zaky Alfian Virady; Mei Retno Adiwati (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
There are still problems in terms of performance making this research the main priority. The purposes of this study to determine the effect of motivation and work discipline on the performance of the employees of Packing Plant Celukan Bawang PT Semen Tonasa. The questionnaire distributed to employees of the Celukan Bawang Packing Plant of PT Semen Tonasa which opened 55 employees was primary data and used a sample of 55 respondents. Saturated sample is used as a sampling technique using a saturated sampling technique. This study uses questionnaires as a data collection method and uses a Likert scale as a measuring tool. Meanwhile, the researchers used Partial Least Square (PLS) as an analytical technique. Based on the results of research conducted that motivation and work discipline individually has a positive and significant effect on employee performance.